Analisis Terhadap Konsep Perjanjian dan Unsur-Unsur Perjanjian dalam Hukum Perikatan - Raynee, Rasheesa Ryash; Ni’matussa’idah, Zulfa Layla; Salsabilasyah, Firyal Nur; K, Karren; S, Surahmad (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Agreements are an important part of the contract law system that is used to regulate the rights and obligations between the parties involved. Agreements create binding relationships and provide legal certainty. The research we conducted aims to further understand the concept of agreements, their elements, and the applicable legal basis. With a normative legal approach, this study examines the things that affect the validity of agreements, such as agreement, the ability of the parties involved, clarity of objects, and objectives that are in accordance with the law. In addition, this study also discusses important principles in contract law, such as the principle of mutual agreement, freedom to make agreements, the obligation to comply with agreements, and good faith, which are a strong basis for implementing agreements. This study found that contract law not only provides certainty and protection for the parties involved, but also provides a way to resolve problems if someone does not fulfill their promise. With the development of society and technology, contract law continues to adapt to remain relevant in maintaining justice and legal certainty in society. The results of this study are expected to be a reference for academics and practitioners to understand and implement valid and binding agreements according to current legal developments.